Persistent acute cholecystitis after cholecystostomy – increased mortality due to treatment approach?. Issue 6 (June 2022) - Hess, Gabriel F.; Sedlaczek, Philipp; Haak, Fabian; Staubli, Sebastian M.; Muenst, Simone; Bolli, Martin; Zech, Christoph J.; Hoffmann, Martin H.; Mechera, Robert; Kollmar, Otto; Soysal, Savas D.
Abstract: Background: Percutaneous cholecystostomy (PC) is a treatment option for acute cholecystitis (AC) in cases where cholecystectomy (CCY) is not feasible due to limited health conditions. The use of PC remains questionable. The aim was to retrospectively analyse the outcome of patients after PC. Methods: All patients who underwent PC for AC at a tertiary referral hospital over 10 years were included. Descriptive statistics, analysed mortality with and without CCY after PC, and a multivariable logistic regression for potential confounder and a landmark sensitivity analysis for immortal time bias were used. Results: Of 158 patients, 79 were treated with PC alone and 79 had PC with subsequent CCY. Without CCY, 48% (38 patients) died compared to 9% with CCY. In the multivariable analysis CCY was associated with 85% lower risk of mortality. The landmark analysis was compatible with the main analyses. Direct PC-complications occurred in 17% patients. Histologically, 22/75 (29%) specimens showed chronic cholecystitis, and 76% AC. Conclusion: Due to the high mortality rate of PC alone, performing up-front CCY is proposed. PC represents no definitive treatment for AC and should remain a short-term solution because of the persistent inflammatory focus. According to these findings, almost all specimens showed persistent inflammation.